The influence of Madurese dialect toward students’ English word stress production - Lusia Eni Puspandari; Yazid Basthomi (Universitas Pendidikan Indonesia, 2022)
Communication using English in Indonesia is challenging, especially when English is not used frequently. It’s happen to some area where English is only taught as mandatory subject in high schools. Madura is one of island in East Java that has unique characteristic, especially in the native language. This study aimed to analyze the misplaced of English word stress done by Madurese students and to find out the reason why they frequently misplace the word stress. A questionnaire and recording were used to collect data about students’ background identity and to record the students’ voice in pronouncing English words. The data were analysed by using qualitative research design to find out the causes of word stress misplacement. The findings revealved that the influence of mother language, motivation, attitude, and age are the most influential factors that generate students in misplacing the word stress. Besides, the lack of pronunciation training and practice done by teachers in their high school was also generating factors for students in pronouncing incorrect word stresses.